Hubungan Penurunan Kadar Natrium Terhadap Gangguan Pola Tidur Pasca TURP (Transurethral Resection of The Prostate) - Khomeini Khomeini; Dody E Dody E; Erkadius Erkadius (Jurnal Kesehatan Andalas, 2013)
AbstrakLatar Belakang. TURP merupakan tindakan operasi endoskopi standar baku untuk penatalaksanaan BPH yang memerlukan tindakan bedah. Dalam pengamatan sehari hari pasien pasca TURP mengeluhkan gangguan pola tidur pasca tindakan. Belum dilaporkan angka kejadian gangguan pola tidur pasca TURP. Salah satu masalah yang mungkin sebab yaitu terjadinya penurunan kadar natrium akibat imbibisi air irigant ke intra vaskuler. Penurunan kadar natrium dapat menyebabkan gangguan neurologis yang mengganggu pola tidur. Penurunan natrium berlanjut dapat menjadi sindroma TURP. Metodologi. Penelitian ini penelitian cross sectional, semua pasien BPH dilakukan pemeriksaan natrium dan diberikan kuesioner gangggan pola tidur. Setelah TURP dilakukan pemeriksaan natrium pasca TURP dan kuesioner kembali. Jumlah distribusi gangguan pola tidur dan kadar natrium disajikan dalam bentuk tabel. Tiap variabel dilakukan analisa dan uji statistik dengan menggunakan T-test, chisquare dan Fisher. Hasil. Didapatkan pasien dengan gangguan pola tidur 41%.. Didapatkan perbedaan bermakna hubungan antara umur pasien dengan gangguan pola tidur pada tabel 3 ( chisquare 1.999027 ). Tidak didapatkan perbedaan bermakna hubungan antara pekerjaan pasien dengan gangguan pola tidur pada tabel 5 (Chi square: 1.242). Tidak didapatkan perbedaan bermakna hubungan antara pendidikan pasien dengan gangguan pola tidur pada tabel 6 (chisquare 1,242). Tidak didapatkan perbedaan bermakna hubungan antara lama operasi dengan gangguan pola tidur tabel 7 (chisquare 3,306). Didapatkan lama operasi <1jam terjadi penurunan kadar natrium 3,783 + 2,235mmol/L sedangkan operasi > 1 jam terjadi penurunan natrium 6,692 + 6,047dengan perbedaan bermakna secara statistic.( t=2,087 ; P 0,044). Tidak didapatkan perbedaan bermakna hubungan antara jumlah cairan irigasi dengan gangguan pola tidur pada tabel 8 ( chi square 2,520). Tidak didapatkan perbedaan bermakna antara jumlah cairan irigasi dengan penurunan natrium pada gambar 2 (F1,35 = 3,004). Didapatkan Mean natrium sebelum TURP 139,3 + 3,7 dan natrium sesudah TURP 134,Kata kunci: Gangguan pola tidur, Penurunan kadar natrium, TURPAbstractBackground. TURP is the gold standard endoscopic surgery for the treatment of benign enlargement of the prostate gland that requires surgery. In daily observations after TURP patients often complain of sleep patterns disturbances . Incidence has not been reported sleep pattern disturbance after TURP. One problem that may cause sodium levels are decreasing as a result of water imbibition irigant to intra vascular. Declining levels of sodium cause neurological disorders that can disrupt sleep patterns. The decline continues of Sodium level could be a TURP syndrome.Methodology. This study is a cross sectional study, all patients with diagnose Benign Prostate Hypertrophi should be check sodium level and get questionnaire sleep patterns disturbances. After TURP check sodium level and questionnaires again . The number of distribution of sleep pattern disturbances and the sodium content is presented in tabular form. Each variabel was analize and statistic test with T-test, Fischer and chisquare.Results. Obtained patients with sleep patterns dsiturbances 41% . Achieved significant differences between relationship age of the patient with sleep patterns disturbances in Table 3 (chisquare 1.999027). No significant differences in the relationship between the work of patients with sleep patterns disturbances in table 5 (Chi square: 1,242). No significant differences in the relationship between the education of patients with sleep patterns dsiturbances in table 6 (chisquare 1.242). No significant differences in the relationship between long operation with sleep pattern disturbance in table 7 (chisquare 3.306). In this research, the operating time <1 hr make a decrease sodium levels 3.783 + 2.235 mmol / L, while operating > 1 hour decrease sodium 6.692 + 6.047 mmol/L with a statistically significant difference. (T = 2.087, P 0.044). No significant differences in the relationship between irrigation fluid with sleep patterns indisturbances table 8 (chi square 2.520). No significant differences between the amount of irrigation fluid with decreased of sodium level in figure 2 (F1, 35 = 3.004). Obtained Mean of sodium before TURP 139.3 + 3.7 and sodium after TURP 134.4 + 5.3 mmol / L. No significant differences between the relationship of sodium before TURP in table 9 (chi square 1.286) and post-TURP with decreased of sodium levels in table 10 (chi square 1.286) with sleep patterns disturbances after TURP. In getting significant differences between sleep patterns disturbances with decreases sodium levels in table 11 (Fischer: 0.0000118)Conclusion. The incidence of sleep patterns disturbances after TURP 41%. Sleep patterns disturbancesb after TURP is associated with decreased levels of sodium and operating time. No significant difference was found between age, occupation, education, with sleep patterns disturbances after TURP.Keywords:sleep patterns disturbances , decrease sodium levels, TURP.